Pulmonary pyruvate metabolism as an index of inflammation and injury in a rat model of acute respiratory distress syndrome. (18th July 2020) - Pourfathi, Mehrdad; Xin, Yi; Rosalino, Michael; Cereda, Maurizio; Kadlecek, Stephen; Duncan, Ian; Profka, Harrilla; Hamedani, Hooman; Siddiqui, Sarmad; Ruppert, Kai; Chatterjee, Shampa; Rizi, Rahim R.
Abstract : Increased pulmonary lactate production is correlated with severity of lung injury and outcome in acute respiratory distress syndrome (ARDS) patients. This study was conducted to investigate the relative contributions of inflammation and hypoxia to the lung's metabolic shift to glycolysis in an experimental animal model of ARDS using hyperpolarized (HP) 13 C MRI. Fifty‐three intubated and mechanically ventilated male rats were imaged using HP 13 C MRI before, and 1, 2.5 and 4 hours after saline (sham) or hydrochloric acid (HCl; 0.5 ml/kg) instillation in the trachea, followed by protective and nonprotective mechanical ventilation (HCl‐PEEP and HCl‐ZEEP) or the start of moderate or severe hypoxia (Hyp90 and Hyp75 groups). Pulmonary and cardiac HP lactate‐to‐pyruvate ratios were compared among groups for different time points. Postmortem histology and immunofluorescence were used to assess lung injury severity and quantify the expression of innate inflammatory markers and local tissue hypoxia. HP pulmonary lactate‐to‐pyruvate ratio progressively increased in rats with lung injury and moderate hypoxia (HCl‐ZEEP), with no significant change in pulmonary lactate‐to‐pyruvate ratio in noninjured but moderately hypoxic rats (Hyp90). Pulmonary lactate‐to‐pyruvate ratio was elevated in otherwise healthy lung tissue only in severe systemic hypoxia (Hyp75 group). ex vivo histological and immunopathological assessment further confirmed the link between elevated glycolysis and the recruitment into and presence of activated neutrophils in injured lungs. HP lactate‐to‐pyruvate ratio is elevated in injured lungs predominantly as a result of increased glycolysis in activated inflammatory cells, but can also increase due to severe inflammation‐induced hypoxia. Abstract : Elevated HP 13 C lactate‐to‐pyruvate ratio observed in rats with lung injury and moderate hypoxemia is primarily caused by the activation of inflammatory cells. Although lung tissue can tolerate moderate reductions in oxygen availability without altering its metabolism, an elevated lactate‐to‐pyruvate ratio may also be caused by severe local hypoxia in the lung tissue as a result of injury and inflammation. HP [1– 13 C] pyruvate MRI can be used to map pulmonary tissue lactate to assess injury severity and monitor therapeutic response.